Applications of social marketing for implementation science: a scoping review - Colquhoun, Heather; Ellen, Moriah E.; Brehaut, Jamie; Weinreich, Nedra K.; Morvinski, Coby; Zarshenas, Sareh; Nguyen, Tram; Presseau, Justin; McCleary, Nicola; Shepherd, Heather A.; Dabbagh, Armaghan; Proctor, Enola (Université d'Ottawa | University of Ottawa, 2025)
Abstract Background Implementation science has a history of drawing from other fields to advance its science, yet understanding how approaches from marketing might enhance the field remains a largely untapped area of theoretical and methodological potential. Social marketing (i.e., applying commercial marketing to solve social or health problems) is a branch of marketing that shares many conceptual features with implementation science (e.g., behaviour change), but remains an unrealized opportunity for synergy. This review aimed to 1) describe studies that have tested social marketing interventions in controlled designs; 2) describe these interventions including their context, mechanism, and outcome; and 3) propose social marketing approaches that might be usefully applied to implementation science. Methods This scoping review, with a team consensus discussion, followed JBI (formerly the Joanna Briggs Institute) methodological guidance and included a team of researchers and practitioners in implementation, marketing, and social marketing. Twelve databases were searched. Studies were included that 1) utilized a randomized or non-randomized controlled intervention design; and 2) tested a social marketing intervention as defined by five essential social marketing criteria. Two reviewers independently completed all screening and extraction. Variables extracted included intervention details per social marketing criteria and the intervention’s context, mechanism, and outcome. Team consensus discussions of the scoping review results were used to determine approaches that might be usefully applied more broadly across implementation science. Results Screening of 4,867 citations yielded 28 included studies published from 1999–2023. All topics were from the health field and included nutrition (13, 46%), sexual health/family planning (6, 21%), physical activity (3, 11%), child safety (1, 4%), cancer screening (1, 4%), fall prevention (1, 4%), worksite safety (1, 4%), sanitation (1, 4%), and substance abuse (1, 4%). Novel theories identified included ‘Exchange Theory’ and ‘Consumer Information Processing Model’. Proposed approaches to consider for application included: leverage emotions; design for appeal; consider what your audience values; understand the price; understand the place; emphasize competitive advantage; and use branding. Conclusions This review examined the application of social marketing theories and approaches to implementation science. Applying social marketing approaches could invigorate novel and creative thinking in implementation science. Registration Open Science Framework Registration link: osf.io/6q834.